Benign prostatic hyperplasia and intraprostatic inflammation are associated with liver inflammation: it's time for prevention. (1st June 2018) - Privitera, S.; Russo, G. I.; La Vignera, S.; Condorelli, R. A.; Calogero, A. E.; Cantiello, F.; Damiano, R.; Favilla, V.; Cimino, S.; Morgia, G.
Summary: Some evidences have supported the link between benign prostatic hyperplasia (BPH)/lower urinary tract symptoms (LUTS) and inflammation. In this study, we aimed to evaluate the association between prostatic inflammation (PI) and non‐alcoholic steatohepatitis (NASH) evaluated by a non‐invasive scores in a cohort of patients affected by BPH/LUTS. Between January 2012 and January 2016, we conducted a prospective study in a single academic outpatient clinic on 132 consecutive patients who underwent surgery for lower urinary tract symptoms (LUTS) due to bladder outlet obstruction (BOO). A non‐invasive non‐alcoholic steatohepatitis score (NASH score) was calculated, and PI was evaluated through the Irani score. Patients with a NASH score > 1.05 had an average larger prostate volume (55 vs. 45 cc, p  < 0.05), a greater waist circumference (103 vs. 93.5 cm, p  < 0.01), and high values of blood glucose, triglycerides, insulin, and BMI compared to patients without NASH; 36% of patients with an Irani score ≥ 4 had NASH compared to 16.1% of patients who had a NASH score < 1.05 ( p  < 0.05). We found that non‐alcoholic steatohepatitis (NASH ≥ 1.05) was an independent risk factor for Irani score ≥4 (OR: 3.24; p  < 0.05) and of prostate volume ≥ 40 cc (OR: 13.99; p  < 0.01). LUTS/BPH and NASH can be closely related, underlying common triggers of induction. In particular, inflammation seems to be associated with both conditions and with prostate gland overgrowth. Early identification of this class of patients could play a key role in preventing complications related to disease progression.